Neutron Diffraction Investigation of the DyFe11Ti Magnetic Structure and Its Spin Reorientations. (February 2020) - Isnard, Olivier; Kinast, Eder J.
Abstract: In this article, we report on the magnetic structure of DyFe11 Ti and its thermal evolution as probed by neutron powder diffraction. A thermodiffraction technique was used to follow the temperature dependence of the magnetic moments, as well as their orientation. The Dy and Fe moments were coupled to each other in an antiparallel manner to form a ferrimagnet, where the easy magnetization direction at 2 K was the [110] axis in the basal ( a, b ) plane. This magnetic structure underwent two successive spin reorientation phenomena with increasing temperature. A large Dy magnetic moment of 9.7 Bohr magneton (μB ) was obtained at low temperatures, and the magnitude decreased rapidly to 7.5μB at 200 K. The largest Fe magnetic moment was observed on the Fe 8 i position. A ThMn12 -type crystal structure was preserved in the studied temperature range, despite the large changes of the magnetic structure. A sharp tilt was observed at the first-order spin reorientation, T SR1 ; the angle between the easy magnetization axis and the crystal c axis was reduced from 90° at 2 K to about 20° at 200 K (where c is the easy axis above 200 K); and the Dy and Fe magnetic moments maintained an antiparallel coupling.